Telehealth in primary mental health care in rural and remote areas: A systematic review - Maria Norberta Bwariat; Ah Yusuf; Rizki Fitryasari PK; Yulia Yunara (Universitas Muhammadiyah Magelang, 2022)
Mental health problems are becoming more prevalent globally. Therefore, innovative patient care delivery approaches are being considered due to the rising need for primary mental health care services and an increase in the usage of digital communication tools online. For this reason, this systematic review was conducted to analyse relevant articles about telehealth in primary mental health care services in rural and remote areas. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) checklist was provided as guidance. The Joanna Briggs Institute (JBI) checklist was also used to evaluate the quality assessment. The databases are Scopus, Web of Sciences, and PubMed databases. Most telehealth in primary mental health care used in rural and remote areas takes the form of videoconferencing and application. Telehealth in primary mental health care services delivered to difficult-to-reach populations, like those in rural and remote areas, has significantly improved community mental health services in terms of results and satisfaction. Tele-mental health can be considered a safe and long-term solution but has several challenges that must be addressed. Keywords: Mental health; primary health care; rural area; remote Area; telehealth